Thalictrum minutiflorum (Ranunculaceae), described from Guizhou province, China, is merged with T. ramosum - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2023)
Based on critical observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that Thalictrum minutiflorum, described from Dejiang county in Guizhou province, China, is conspecific with T. ramosum, a species widely distributed in China’s Chongqing, northwestern Guangxi, Guizhou, western Hubei, western Hunan, central and southwestern Sichuan and northeastern Yunnan. We therefore reduce T. minutiflorum to the synonymy of T. ramosum herein. The description of hairiness is added for T. ramosum, which has been previously described as glabrous throughout. Mistakes in the documentation of collection information including collection localities and collection number of T. ramosum are corrected. Previous misidentifications of specimens of T. ramosum and the resultant wrong records of geographical distribution of this species are also corrected.